Edible Nanocoating: The effect of different starch-based materials incorporated with nanoparticles on the antimicrobial activity / Nurul Jannah Ruzlan ... [et al.] - Ruzlan, Nurul Jannah; Asli, Noor Asnida; Tan, Eddie Ti Tjih; Abdul Muttalib, Siti Azima; Hajar, Nadya (2021)
The application of starch-based film is extensively used as fruit coating in the agricultural sector in the assurance of postharvest quality. A starch-based film such as cassava, corn, and rice film can provide a semi-permeable barrier to moisture and water vapour, however poor in mechanical strength. Thus, several attempts have been made to overcome this limitation by incorporating metal-based antimicrobial agents such as zinc, silver, and titanium into the starch- based coating at the fruit's outer layer. Although extensive study is being done in this field, the comprehensive review focussing on the antimicrobial activity of metal-starch nanocomposite is still lacking. Hence, this study aims to review the effectiveness of different starch materials incorporated with a different metal-based antimicrobial agent as edible nanocoating in the assurance of the postharvest quality of fruits. Zinc oxide nanoparticles (ZnONP), silver nanoparticles (AgNP), and titanium dioxide nanoparticles (TiO2NP) incorporated into cassava, rice, sago, and corn exhibited antimicrobial activity. Therefore, a comprehensive study on the inhibition of metal-starch-based nanocomposite on fungal that affects the post-harvest quality of fruit is recommended.